Female Leadership, Democratization, and Firm Innovation: Social Inequalities and Gender Issues in Post-Communist Economies. Issue 2 (4th March 2022) - Iman, Adrita; Nazarov, Zafar; Obydenkova, Anastassia
ABSTRACT: Do women exhibit a different pattern of entrepreneurial behavior as compared to men in post-Communist societies? This paper addresses this question using survey data from 25 Eastern Europe and Central Asian states. The sample consists of 11, 617 private firms. As a result of 11, 000 observations and multiple robustness checks, we find that female owners are more likely to introduce new marketing strategies than males. We demonstrate that firm innovation increases among top female managers with the increase in democratization. Democratization eliminates the gender disadvantages in firm innovation for most types of firm innovation. HIGHLIGHTS: For most definitions, female leaders perform equally to males in firm innovation. Female owners have a slightly higher tendency to introduce new marketing strategies than males. Female top managers are less likely to invest in Research and Development as compared to male managers. Firm innovation increases among top female managers with the increase in democratization. Democratization eliminates the gender disadvantages in firm innovation for most types of innovation.